The crystal structure of hexaquazinc(II) poly[hexakis(μ2-4-methylbenzenesulfinato-κ2O:O′) dizinc(II)] - Xi-Shi Tai; Xi-Hai Yan; Yuan-Fang Wang; Li-Hua Wang (Zeitschrift für Kristallographie - New Crystal Structures, 2024)
C42H54O18S6Zn3, trigonal, P3‾1m $P\overline{3}1m$ (no. 162), a = 9.2916(13) Å, c = 18.121(4) Å, V = 1354.9(5) Å3, Z = 0.99996, R gt(F) = 0.0490, wR ref(F 2) = 0.1330, T = 293(2) K.